Bond Performance of Carbon Fiber-Reinforced Polymer Bar with Dual Functions of Reinforcement and Cathodic Protection for Reinforced Concrete Structures. (25th January 2020) - Zhou, Yingwu; Sui, Lili; Xing, Feng; Huang, Xiaoxu; Zheng, Yaowei; Zhao, Debo
Abstract : The dual function of a carbon fiber-reinforced polymer (CFRP) bar working as reinforcement and impressed current cathodic protection (ICCP) anode for reinforced concrete structures has been proposed and researched in this paper. The ICCP tests with different current densities and polarization durations were first conducted for the concrete with high chloride content. After the ICCP application, pull out tests were then performed to investigate the bond behaviors of CFRP bars. Experimental results have shown the effectiveness of the new-type ICCP system with the CFRP bar as the anode on corrosion protection. The ICCP system provided electrons to the steel bar continuously and brought the potential of the steel bar down to the immunity region. Under the anodic polarization with a large current density of 100 mA/m 2, the CFRP bar-concrete interface presented acidification and the chemical adhesion on the interface was decreased significantly. However, for cases in the experiment, the ICCP application had an insignificant influence on the ultimate bond strength.